SOSIALISASI PEMANFAATAN NASI BASI MENJADI PUPUK ORGANIK SEBAGAI MIKRO ORAGNISME LOKAL MENJADI PUPUK CAIR ORGANIK DI GAMPONG COT CUT KECAMATAN KUTA BARO, KABUPATEN ACEH BESAR: Sosialisasi Pemanfaatan Nasi Basi menjadi Pupuk Cair Organik - Teuku Fadhla Ali; Muhammad Nasir Ismail; Dedhi Yustendi; Zahrul Fuadi; Mulyadi (Mejuajua: Jurnal Pengabdian pada Masyarakat, 2022)
The community service Program by students and accompanied by Abulyatama lecturers in the post-covid-19 edition is specifically designed as a solution to the implementation of community service programs. This activity was born from the premise that students are prospective scholars as successors of development who can also work to solve development problems that exist in society. This Program was conducted on the cot Cut Gampong in Kuta Baro district with an area of 228.00 Ha, a population of 803 people. While the plan of activities as follows general field (i) Bersilaturrahmi and socialize with the community about the socialization of utilization of stale rice into organic fertilizer. The benefits of the utilization program of stale rice into liquid organic fertilizer is to provide counseling and assistance to the community about its use as organic fertilizer and overcome waste management from households, namely stale rice that can be used for plant fertilizer and can reduce the cost of rural communities in managing their farming.